2012
DOI: 10.1016/j.jcmg.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Individuals With a Positive Family History for Premature Coronary Artery Disease and Elevated Coronary Calcium Scores Benefit From Statin Treatment

Abstract: The combination of a positive family history and CCS above the 80th percentile identifies a subgroup within the primary prevention population that receives greater benefit from statin treatment than the population at large. These results have important implications for future guidelines concerning individuals with a positive family history for premature CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 34 publications
(18 reference statements)
2
18
0
Order By: Relevance
“…7 Despite the fact that the outcome of the St. Francis Heart trial, which investigated the effect of atorvastatin 20 mg/day in asymptomatic individuals with a CAC score above the 80th percentile, did not reach statistical significance, a post hoc analysis showed that the combination of a positive family history and a CAC score above the 80th percentile was a subgroup within the primary-prevention population that received greater benefit from statin treatment than the population at large. 24 Our study has certain limitations. First, the number of subjects was relatively small, so subgroup analysis to identify subsets that may have benefited more from atorvastatin treatment could not be performed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…7 Despite the fact that the outcome of the St. Francis Heart trial, which investigated the effect of atorvastatin 20 mg/day in asymptomatic individuals with a CAC score above the 80th percentile, did not reach statistical significance, a post hoc analysis showed that the combination of a positive family history and a CAC score above the 80th percentile was a subgroup within the primary-prevention population that received greater benefit from statin treatment than the population at large. 24 Our study has certain limitations. First, the number of subjects was relatively small, so subgroup analysis to identify subsets that may have benefited more from atorvastatin treatment could not be performed.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the proportion of subjects who normalized endothelial function (RHI ≥2) after atorvastatin and placebo treatment was not significantly different (40% vs 37%, P = 1.000) (Figure 3). The augmentation index after atorvastatin treatment was not different from that after placebo treatment (24 [IQR, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs 29 [IQR 16-35], P = 0.922). In the subgroup analysis, these results were consistent both in subjects indicated for drug therapy (11 subjects, 31%) and subjects not indicated for drug therapy (24 subjects, 69%), according to the NCEP-ATP III guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies were likely underpowered to detect a difference in CAC progression, and participants had very elevated baseline CAC scores, which makes interpretation of CAC progression more challenging. Interestingly, a recently completed post-hoc analysis of the St. Francis Heart Study found a significant reduction in CHD events with statin treatment for participants with a family history of premature CHD and elevated baseline CAC scores, although CAC score change was not examined in this analysis [39]. It would be interesting to see if individuals with varying degrees of risk factors, including extent of family history and CAC, demonstrate a risk-factor- and score-dependent relationship to statin response.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with young CAD high C-reactive protein have been associated recurrence of future acute coronary event and raised fibrinogen levels seems to be associated with increased mortality[6]. Persons with positive family history of premature CAD and coronary artery calcium scores greater than 80 th percentiles benefit from treatment with statins for primary prevention of acute coronary events[68]. …”
Section: Prognosismentioning
confidence: 99%